3D modelling of Trompsburg Complex (in South Africa) using 3D focusing inversion of gravity data. (June 2017) - Rezaie, Mohammad; Moradzadeh, Ali; Kalate, Ali Nejati; Aghajani, Hamid; Kahoo, Amin Roshandel; Moazam, Sahar
Abstract: The Trompsburg complex is a huge layered mafic igneous rock that is located near the town of Trompsburg in the Free State Province, South Africa that does not outcrop on the surface. Here, we construct 3D model of Trompsburg intrusion using 3D focusing inversion of gravity data. The inversion of gravity data is one of the most important topics in the quantitative interpretation of practical geophysical data. Focusing inversion can produce compact solution and recover the sharp boundaries between intrusive body and host rocks. In focusing inversion of Trompsburg gravity data we set focusing parameter equals 0.02. According to the geological information, lower density bound set to −0.1 g/cm 3 and upper density bound set to 0.5 g/cm 3 . The results of 3D inversion in this study indicate that the Trompsburg Complex is a deep bowl-shaped intrusion which is extended to 33(km) below the surface. It is like an oval in horizontal plane sections with major axis of nearly 50 km in west- east direction and north- south minor axis about 30 km. The obtained results confirms that this complex could be related to intraplate magmatism. Highlights: 3D focusing inversion of gravity data can be used for 3D modelling of deep structures in earth crust. 3D model of Trompsburg complex has been achieved using 3D focusing inversion of gravity data. Trompsburg intrusion is a deep bowl-shaped oval intrusive body which is extended to 33 km of crust. Trompsburg intrusion is related to intraplate magmatism occurred by a super-plume event.